Parental Depression and Anxiety Associated with Newborn Bloodspot Screening for Rare and Variable-Onset Disorders - Natalie A. Boychuk; Niamh S. Mulrooney; Nicole R. Kelly; Aaron J. Goldenberg; Ellen J. Silver; Melissa P. Wasserstein (MDPI AG, 2022)
The ability to screen newborns for a larger number of disorders, including many with variable phenotypes, is prompting debate regarding the psychosocial impact of expanded newborn bloodspot screening (NBS) on parents. This study compares psychological outcomes of parents of children with a range of NBS/diagnostic experiences, with a particular focus on lysosomal storage disorders (LSDs) and X-linked adrenoleukodystrophy (X-ALD) as representative disorders with complex presentations. An online cross-sectional survey with six domains was completed in 2019 by a volunteer sample of parents with at least one child born between 2013 and 2018. Parents were classified in the analysis stage into four groups based on their child's rare disorder and means of diagnosis. Stress and depression were estimated using dichotomous measures of the depression subscale of the Hospital Anxiety and Depression Scale and the Parental Stress Scale. Logistic regression models were estimated for the relationship between the parent group and stress/depression, controlling for demographic variables (region of the US, income, education, major life events, relationship to the child, number of children, parent age, and race/ethnicity). One hundred seventy-four parents were included in this analysis. Parents of children with an LSD or X-ALD diagnosis clinically may have higher odds of depression (OR: 6.06, 95% CI: 1.64-24.96) compared to parents of children with the same disorders identified through NBS, controlling for covariates. Although a similar pattern was observed for parental stress (OR: 2.85, 95% CI: 0.82-10.37), this did not reach statistical significance. Ethically expanding NBS and genome sequencing require an understanding of the impacts of early detection for complex disorders on families. These initial findings are reassuring, and may have implications as NBS expands. Given our small sample size, it is difficult to generalize these findings to all families. These preliminary trends warrant further investigation in larger and more diverse populations.